2019
DOI: 10.1080/17476348.2019.1601559
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of chronic obstructive pulmonary disease

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is a heterogeneous condition, which presents the opportunity for precision therapy based on genetics or other biomarkers. Areas covered: Alpha-1 antitrypsin deficiency, a genetic form of emphysema, provides an example of this precision approach to diagnosis and therapy. To date, research in COPD pharmacogenomics has been limited by small sample sizes, lack of accessible target tissue, failure to consider COPD subtypes, and different outcomes relevant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
0
5
0
2
Order By: Relevance
“…Os medicamentos que constituem a base da terapia sintomática são os broncodilatadores, sendo eles beta-2-agonistas de ação curta e beta-2-agonistas de ação prolongada (LABAs), além de antagonistas muscarínicos de ação curta e antagonistas muscarínicos de ação prolongada (LAMAs). Em caso de medicação de resgate usa-se mais os beta-2-agonistas de ação curta, já o uso dos broncodilatadores de ação prolongada corresponde Brazilian Journal of Health Review, Curitiba, v. 7, n. 2, p. 01-09, mar./apr., 2024 a um meio mais eficaz de reduzir os sintomas com um efeito adicional de prevenir exacerbações (Hersh, 2019;Sandelowsky et al, 2021).…”
Section: Tratamentounclassified
See 1 more Smart Citation
“…Os medicamentos que constituem a base da terapia sintomática são os broncodilatadores, sendo eles beta-2-agonistas de ação curta e beta-2-agonistas de ação prolongada (LABAs), além de antagonistas muscarínicos de ação curta e antagonistas muscarínicos de ação prolongada (LAMAs). Em caso de medicação de resgate usa-se mais os beta-2-agonistas de ação curta, já o uso dos broncodilatadores de ação prolongada corresponde Brazilian Journal of Health Review, Curitiba, v. 7, n. 2, p. 01-09, mar./apr., 2024 a um meio mais eficaz de reduzir os sintomas com um efeito adicional de prevenir exacerbações (Hersh, 2019;Sandelowsky et al, 2021).…”
Section: Tratamentounclassified
“…Pode ser usado também a combinação de corticoides inalatório (CI) com um LABA ou LABA + LAMA (terapia tripla) nos pacientes que apresentaram duas ou mais exacerbações no ano anterior e uma ou mais hospitalização por exacerbação de DPOC (Ferrera;Labaki;Han, 2021) Além disso, a combinação de um corticoide inalatório com um LABA ou com uma combinação de LAMA + LABA reduz significamente as exacerbações em maior extensão do que o uso de broncodilatadores isolados. O tratamento com terapia tripla de CI + LABA + LAMA em dose fixa, nos pacientes sintomáticos com DPOC e com histórico de exacerbação, reduziu consideravelmente as taxas de exacerbações moderadas ou graves da DPOC, melhorou também a função pulmonar, reduziu os sintomas e melhorou a qualidade de vida relacionada à saúde, quando comparada com o tratamento duplo de LABA + LAMA ou CI + LABA (Hersh, 2019;Sandelowsky et al, 2021).…”
Section: Tratamentounclassified
“…In brief, precision medicine approach aims to identify and connect the right treatment to the right patient, meanwhile minimizing the risk of adverse effects. Recent studies have identified several treatable features for different types of COPD including pulmonary, extra-pulmonary, psychological, and environmental traits (Hersh, 2019;Dennett et al, 2021). The next step is identifying and quantifying physiological features, molecular pathways and underlying mechanisms of these treatable traits through innovative modeling or detection techniques and then developing noble reliable point-of-care biomarkers to predict and/or differentiate responders from nonresponders to targeted therapies or precision medicine (Wouters et al, 2017;Cazzola et al, 2018;Sidhaye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, precision medicine approach aims to identify and connect the right treatment to the right patient, meanwhile minimizing the risk of adverse effects. Recent studies have identified several treatable features for different types of COPD including pulmonary, extra-pulmonary, psychological, and environmental traits ( Hersh, 2019 ; Dennett et al, 2021 ). The next step is identifying and quantifying physiological features, molecular pathways and underlying mechanisms of these treatable traits through innovative modeling or detection techniques and then developing noble reliable point-of-care biomarkers to predict and/or differentiate responders from non-responders to targeted therapies or precision medicine ( Wouters et al, 2017 ; Cazzola et al, 2018 ; Sidhaye et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%